Recent Developments in Data Independent Acquisition (DIA) Mass Spectrometry: Application of Quantitative Analysis of the Brain Proteome - Li, Ka Wan; Gonzalez-Lozano, Miguel A.; Koopmans, Frank; Smit, August B. (Frontiers in Molecular Neuroscience, 2020)
Mass spectrometry is the driving force of current brain proteome analysis. In a typical proteomics approach, a protein isolate is digested into tryptic peptides and then analysed by liquid chromatography–mass spectrometry. The recent advancement of data independent acquisition (DIA) mass spectrometry provides higher sensitivity and protein coverage than the classic data dependent acquisition. DIA cycles through a pre-defined set of peptide precursor isolation windows stepping through 400-1200 m/z across the whole liquid chromatography gradient. All peptides within an isolation window are fragmented simultaneously and detected by tandem mass spectrometry. Peptides are identified by matching the ion peaks in a mass spectrum to a spectral library that contains information of the peptide fragment ions pattern and its chromatography elution time. Currently, there are several reports of DIA in brain research, in particular the quantitative analysis of cellular and synaptic proteomes to reveal the spatial and/or temporal changes of proteins that underlie neuronal plasticity and disease mechanisms. Protocols in DIA are continuously improved in both acquisition and data analysis. The depth of analysis is currently approaching proteome-wide coverage, while maintaining high reproducibility in a stable and standardisable MS environment. DIA can be positioned as the method of choice for routine proteome analysis in basic brain research and clinical applications.